Green Synthesis of Halo-Substituted Chalcones as Potential Enzyme Inhibitors: A Molecular Docking Study - Parveen Rani (International Journal of Engineering Science & Humanities, 2026)
Chalcones represent an important class of bioactive compounds with diverse pharmacological properties and the development of sustainable synthetic strategies for their production remains a key focus in green medicinal chemistry. In the present study, thirty-two halo-substituted chalcone derivatives were synthesized through the Claisen–Schmidt condensation reaction employing four environmentally friendly activation techniques: mechanochemical grinding, thermal heating, microwave irradiation and neat-melt activation. Each method was utilized to synthesize eight derivatives, enabling a comparative assessment of their synthetic efficiency and biological significance. The synthesized compounds were purified and characterized using standard analytical techniques. Their inhibitory activity against α-amylase and trypsin enzymes was evaluated, revealing measurable inhibition for all derivatives with significant structure-dependent variations. Certain compounds exhibited enhanced inhibitory activity, highlighting the influence of halogen substitution and aromatic conjugation on enzyme modulation. Molecular docking studies were conducted to investigate ligand–enzyme interactions and validate experimental findings, demonstrating favorable binding affinities and stable interactions within the active sites of both enzymes. The results further indicated that enzymatic activity and docking performance were independent of isolated yields, emphasizing the dominant role of molecular structure over synthetic efficiency in determining biological activity. Overall, this study integrates green synthesis, biological evaluation and computational analysis, establishing halo-substituted chalcones as promising candidates for future therapeutic development.